Enhanced acquisition of antibiotic-resistant intestinal E. coli during the first year of life assessed in a prospective cohort study - Benjamin Hetzer (2019)
© 2019 The Author(s). Background: Increasing bacterial resistance to antibiotics is a serious problem worldwide. We sought to record the acquisition of antibiotic-resistant Escherichia coli (E. coli) in healthy infants in Northern Thailand and investigated potential determinants. Methods: Stool samples from 142 infants after birth, at ages 2wk, 2mo, 4 to 6mo, and 1y, and parent stool samples were screened for E. coli resistance to tetracycline, ampicillin, co-trimoxazole, and cefazoline by culture, and isolates were further investigated for multiresistance by disc diffusion method. Pulsed-field gel electrophoresis was performed to identify persistent and transmitted strains. Genetic comparison of resistant and transmitted strains was done by multilocus sequence typing (MLST) and strains were further investigated for extra- and intra-intestinal virulence factors by multiplex PCR. Results: Forty-seven (33%) neonatal meconium samples contained resistant E. coli. Prevalence increased continuously: After 1y, resistance proportion (tetracycline 80%, ampicillin 72%, co-trimoxazole 66%, cefazoline 35%) almost matched those in parents. In 8 infants (6%), identical E. coli strains were found in at least 3 sampling time points (suggesting persistence). Transmission of resistant E. coli from parents to child was observed in only 8 families. MLST showed high diversity. We could not identify any virulence genes or factors associated with persistence, or transmission of resistant E. coli. Full-term, vaginal birth and birth in rural hospital were identified as risk factors for early childhood colonization with resistant E. coli. Conclusion: One third of healthy Thai neonates harboured antibiotic-resistant E. coli in meconium. The proportion of resistant E. coli increased during the first year of life almost reaching the value in adults. We hypothesize that enhancement of infection control measures and cautious use of antibiotics may help to control further increase of resistance.